164k views
0 votes
Write an exponential expression that is equivalent to (4^14)^-2



THANK UUU

1 Answer

3 votes

(4^14)^-2


=(4^(14))^(-2)

Apply the formula :
(x^m)^n=x^(m*n)

We get:


=4^(14*(-2))


=4^(-28)


=(2^2)^(-28)


=(2^2)^(-28)

Apply the formula :
(x^m)^n=x^(m*n)

We get:


=2^(2*(-28))


=2^(-56)

convert negative exponent into positive


=(1)/(2^(56))

Hence final equivalent answer is
(1)/(2^(56))

You can also use
2^(-56) as exponent form if you don't want to remove negative sign from exponent.

User Stamster
by
6.1k points